De Novo Mutation of Paternal IGF2 Gene Causing Silver–Russell Syndrome in a Sporadic Patient - Liu, Deguo; Wang, Yajian; Yang, Xiu-An; Liu, Deyun (Frontiers in Genetics, 2017)
Silver–Russell syndrome (SRS) is a rare, but well-recognized disease characterized by growth disorder. To date, there are two reports arguing IGF2 mutation for the onset of SRS. Herein, we present another sporadic case harboring IGF2 mutation. The male proband was the first and only child of a non-consanguineous Chinese couple. He was small for gestational age, with relative macrocephaly at birth. Severe feeding difficulties, low feeding, and growth retardation were revealed during neonatal period. At 4.5 years old, obvious body asymmetry was noted. Whole exome sequencing identified a novel de novo c.101G > A (p.Gly34Asp, NM_000612) variant in IGF2 and Sanger sequencing validated the variant. Amplification refractory mutation system polymerase chain reaction demonstrated that the IGF2 variant was on the paternal allele. Alignment shows the variant is evolutionarily conserved. Structural modeling argues that the variant site might be important for the binding of IGF2 to its receptor. Our study provides further evidence that IGF2 mutation may be another mechanism of SRS, and we consider that IGF2 should be included in a disease specific gene panel in case it is designed for SRS routine diagnostics.